Effects of yoga on depressive symptoms, anxiety, sleep quality, and mood in patients with rheumatic diseases: Systematic review and meta-analysis - de Orleans Casagrande P.* (2023)
© 2022 American Academy of Physical Medicine and Rehabilitation.Objective: To investigate the effects of yoga on depressive symptoms, anxiety, sleep quality, and mood of patients with rheumatic diseases through a systematic literature review with meta-analysis. Literature Survey: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement and the Cochrane recommendations and risk of bias tool. The study was registered in the International Prospective Register of Systematic Reviews (PROSPERO). Studies were selected using the PICOS (participants, intervention, comparison, outcome, and study) strategy. Searches were carried out until March 2022 and performed in Web of Science, PubMed, SportDiscus, Scopus, Cochrane, and EBSCO databases. Methodology: Data were extracted to identify the differences between yoga and control and exercise groups and effect sizes. Synthesis: In total, 27 studies were included for qualitative analysis and 18 for meta-analysis. The studies found investigated yoga in patients with osteoarthritis, fibromyalgia, rheumatoid arthritis, and chronic fatigue syndrome. Regarding the risk of bias, the majority of studies showed a high risk or uncertain risk of bias in several criteria. Regarding the meta-analysis, yoga was favored to decrease depressive symptoms (standard mean difference [SMD]:−0.88; 95% confidence interval [CI]:−1.42; −0.34), anxiety (SMD: −0.51; 95% CI = −0.81 to −0.20), and improve sleep quality SMD = −0.96; 95% CI = −1.36 to −0.56). No differences were found between yoga and other exercise modalities in depression (p <.01). Conclusions: Yoga is effective in improving depression, anxiety, and sleep quality of patients with rheumatic diseases. However, research in this field still needs further studies, because of methodological issues in the studies and a reduced number of studies conducted on each rheumatic disease and on the effects of yoga on each variable.